Pharmacogenomics of metabolic effects of rosiglitazone. (February 2008) - ŠŠeda, Ondrej; ŠŠedováá, Lucie; Oliyarnyk, Olena; Kazdováá, Ludmila; Køøenováá, Drahomííra; Corbeil, Gilles; Hamet, Pavel; Tremblay, Johanne; Køøen, Vladimíír
Introduction: Thiazolidinediones are increasingly used drugs for the treatment of Type  2 diabetes. The individual response to thiazolidinedione therapy, ranging from the variable degree of metabolic improvement to harmful side-effects, is empirical, yet the underlying mechanisms remain elusive. In order to assess the pharmacogenomic component of thiazolidinediones'' metabolic action, we compared the effect of rosiglitazone in two genetically defined models of metabolic syndrome, polydactylous (PD) and BN.SHR4 inbred rat strains, with their insulin-sensitive, normolipidemic counterpart, the Brown Norway (BN) rat.Materials & Methods: 5-month-old male rats were fed a high-fat diet for 4  weeks, and the experimental groups received rosiglitazone (0.4  mg/100  g body weight) during the last 2  weeks of high-fat diet feeding. We assessed metabolic and morphometric profiles, oxidative stress parameters and gene expression in white adipose tissue.Results: In many followed parameters, we observed genetic background-specific effects of rosiglitazone administration. The mass and the sensitivity of visceral adipose tissue to insulin-stimulated lipogenesis increased with rosiglitazone treatment only in PD, correlating with a PD-specific significant increase in expression of prostaglandin D2 synthase. The glucose tolerance was enhanced in all strains, although fasting plasma glucose was increased by rosiglitazone in BN and BN.SHR4. Among the markers of lipid peroxidation, we observed the rosiglitazone-driven increase of plasma-conjugated dienes only in BN.SHR4. The genes with genotype-specific expression change included ADAM metallopeptidase domain 7, aquaporin 9, carnitine palmitoyltransferase 1B, caveolin 1, catechol- O -methyl transferase, leptin and prostaglandin D2 synthase 2.Conclusion: Rosiglitazone''s effects on lipid deposition and insulin sensitivity of peripheral tissues are largely dependent on the genetic background it acts upon.